Complications associated with Ventricle-Peritoneal Shunts: Experience at Carlos Van Buren Hospital (2020 –2023) - Villarroel Pedreros, Mauricio Alejandro; Nuñez, Nicolas Bravo (Journal of Neonatal Surgery, 2025)
Ventricle-peritoneal shunt (PVD) is one of the most commonly used surgical procedures for the management of symptomatic hydrocephalus. This surgical procedure is not without complications, both in the short and long term. The literature shows varied and dissimilar reports regarding the incidence of complications of these. The purpose of this work is to know the local reality of complications in the Neurosurgery service of the Carlos Van Buren Hospital during the period between March 2020 and April 2023, investigating the incidence and categorizing the complications of PVD and comparing it with that described in the literature. Likewise, as a second objective, to know the incidence and infectious etiology of these procedures. This is intended to provide information so that in the future protocols can be drafted and executed in order to reduce the incidence of complications.